دور وسائل القانون الدولي في حل النزاعات المسلحة : ليبيا أنموذجا : دراسة تحليلية - مجبري، علي عبد الله علي
This research aims at defining alternative dispute resolution methods, studying the criteria and rules that distinguish each of them, examining its appropriateness to the Libyan context, and the way that it could be applied to resolve that dispute. The research employs a deduction and analytical approach. It examines the concept of international negotiations and its importance, the nature, and rules of international mediation, international arbitration, and international organizations and its dispute resolution mechanisms. The research studies alternative dispute resolution methods in Libyan law and modern Libyan disputes. The nature of the dispute and its reasons and the most appropriate alternative methods were analyzed. The study finds that international envoys’ mediation efforts failed because of the delicate nature of the Libyan social unity racially, religiously, tribally, and regionally. Mediators didn’t take into account the previous factors and failed to adhere to the principles of alternative dispute resolution methods the most important of which is to include influential parties in the process of negotiation, the impartiality of international mediators, and training locals to pursue the efforts of mediation supported by international organizations. In addition to the fact that the Libyan society is sensitive to any foreign mediation and desires an entirely local solution. The research finds that negotiation is one of the most important mechanisms to solve the Libyan conflict because it involves direct dialogue between the two parties. Mediation is also the best option to solve the political and armed dispute. It is also possible to resort to arbitration to solve problems related to the violation of rights. When parties fail to solve through negotiation and mediation, refer dispute cases to the permanent court of arbitration in The Hague. The research proposes several recommendations to resolve the dispute in Libya. The most important of these is that the solution should be internally using a strategy of intra-Libyan negotiation mediated by an impartial international party accompanied by pressure on the parties who refuse to adhere to the solution. In addition to including all Libyan parties to arrive at an inclusive, comprehensive, and consensual solution. The international mediator should avoid exercising any authority more than pushing the parties to engage in an intra-Libyan dialogue.